Uji Kandungan Logam Berat Pb Dan Hg Pada Air, Sedimen Dan Lamun (Enhalus acoroides) Di Perairan Teluk Kayeli Kabupaten Buru Provinsi Maluku - Nur Alim Natsir; Debby A. J Selanno; Ch.I. Tupan; Y.T. Male (BIOSEL (Biology Science and Education): Jurnal Penelitian Science dan Pendidikan, 2019)
The difference in accumulation of lead and mercury heavy metals in water, sediments and seagrass organs Enhalus acoroides (roots, rhizomes and leaves) is found in the waters of Kayeli Bay, Buru Island, Maluku Province. Samples were taken from ten observed station (Kayeli River Estuary, Suket River Estuary, Anahoni River Estuary, Waelata I Estuary, Waelata River Estuary II, Waeapo River Estuary, Sanleko River Estuary, Marlosso River Estuary, Nametek Beach and Jikumerasa Beach). Pb and Hg were analyzed using Atomic Absorption Spectrophotometer. The content of Pb and Hg in sediments is higher than in water. The highest Pb and Hg content is found in the roots then in the rhizoma and leaves (roots> rhizoma> leaves). Seagrass Enhalus acoroides is one of the living organisms that can be used as a bio-indicator of the level of heavy metal pollution in the aquatic environment. Key Words: Enhalus acoroides, Pb, Hg, Bioakumulasi, Bioindicator